2018
DOI: 10.22460/project.v1i3.p235-240
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English Vocabulary Using Crossword Puzzle Game at the Seventh Grade Students

Abstract: Teaching English is one of activity in the classroom. A game can use to improve students’ vocabularies mastery in the process of teaching learning, so students do not get bored while studying English. This research is attempted to verify the effectiveness of the Crossword Puzzle Game in teaching vocabulary at the seventh grade students of SMPN 10 Cimahi. The main objective is to figure out whether the crossword puzzle game is effective to improve the students’ vocabularies or not. The method is used quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 0 publications
2
14
0
1
Order By: Relevance
“…Before students study about four aspects in Language student should master vocabulary first in order that makes it easier for them to learn the four aspects of the language. This statement supported by Richard (2001:4) in Anwar and Efransyah (2018) cited in Sadiyah, Septiani, and Kareviati (2019) vocabulary is one of the most obvious components of language and one of the first things applied linguists turned their attention to. In reality, most of the students still lack in mastering vocabulary.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Before students study about four aspects in Language student should master vocabulary first in order that makes it easier for them to learn the four aspects of the language. This statement supported by Richard (2001:4) in Anwar and Efransyah (2018) cited in Sadiyah, Septiani, and Kareviati (2019) vocabulary is one of the most obvious components of language and one of the first things applied linguists turned their attention to. In reality, most of the students still lack in mastering vocabulary.…”
Section: Introductionmentioning
confidence: 89%
“…Montgomey (2007) as cited inAnwar and Efransyah (2018) states that there is a list of kinds vocabulary, where each type of vocabulary has a different purpose and vocabulary development in one facilities growth in another.1. Speaking Vocabulary.…”
mentioning
confidence: 99%
“…They discovered that EFL learners were able to enrich their vocabulary more efficiently through color-coding technique since a higher degree of enjoyment and motivation assisted them to memorize some challenging words. Another interesting study was also accomplished by Anwar and Efransyah (2018). They found that crossword puzzle game increased EFL learners' perseverance and eagerness to expand their second language words mastery continuously since the learners did not get bored easily while engaging in this game.…”
Section: Introductionmentioning
confidence: 97%
“…Anwar and Efransyah also prove this in their article. Anwar and Efransyah (2018) explain that vocabulary is an essential aspect of learning a language because it delivers the meaning used by humans to communicate. In addition, Nugroho and Suprapto (2018) point out that students should have lots of vocabulary in learning a new language.…”
Section: Introductionmentioning
confidence: 99%